2020
DOI: 10.12968/jowc.2020.29.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Use of autologous platelet-rich plasma in healing skin graft donor sites

Abstract: Objective: To demonstrate that the use of platelet-rich plasma (PRP) enhances both the quality of healing and the time required for wound healing at a skin graft donor site. Methods: Patients who had dermo-epidermal skin grafts taken from the thigh area were included in a prospective, randomised clinical study. PRP was applied to one donor site and then covered with Vaseline-impregnated, open-weave gauze and gauze, while the contralateral donor site on the other thigh served as a control and was covered with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Two randomized controlled trials (RCTs) compared PRP application to conventional fixation with split-thickness skin grafts (STSGs) [15, 16]. In 1 case, PRP was applied to the donor site to accelerate wound healing [17]. Two studies aimed to reduce postoperative complications after breast reconstruction with PRP application [18, 19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized controlled trials (RCTs) compared PRP application to conventional fixation with split-thickness skin grafts (STSGs) [15, 16]. In 1 case, PRP was applied to the donor site to accelerate wound healing [17]. Two studies aimed to reduce postoperative complications after breast reconstruction with PRP application [18, 19].…”
Section: Resultsmentioning
confidence: 99%
“…Many factors had to be considered, such as differences in number of PRP applications or the use of activators. In seventeen studies [10, 11, 13-15, 21, 24, 27, 31, 34, 35, 38, 40-42, 50, 53], double spin centrifugation was performed, 21 studies used a single spin protocol [16, 17, 19-23, 29, 30, 32, 33, 36, 37, 43-49, 51, 58], and twelve authors merely disclosed the name of the device used, or no information about this process at all [12, 18, 25, 26, 28, 39, 52, 54-57, 59]. Twenty-two authors reported the use of CaCl and/or Thrb for platelet activation [11, 13-15, 18, 19, 21, 24, 28, 30, 31, 37, 39, 42-47, 50, 51, 58].…”
Section: Resultsmentioning
confidence: 99%
“…Serotonin is seen to promote cell migration, proliferation, survival, and antiapoptotic effects in keratinocytes and fibroblasts [53]. Moreover, numerous lines of evidence also suggest that autologous platelets enhance healing of skin wounds in humans [54]. Platelets are significant reservoirs for serotonin, and the mechanism could be serotoninmediated adhesion and migration of cells involved in tissue repair.…”
Section: Adhesion Migration and Cytoskeletal Remodeling Of Immune Cellsmentioning
confidence: 99%
“…20 Two studies showed that the application of L-PRP and L-PRF to split thickness skin graft donor sites improved healing time and postoperative scarring significantly in patients in whom platelet preparation was applied to the donor site at the time of harvest. 21,22…”
Section: Wound Healingmentioning
confidence: 99%